The Romantic Sublime Studies in the Structure and Psychology of Transcendence - Weiskel, Thomas (Johns Hopkins University Press, 2019)
Originally published in 1976. In The Romantic Sublime Thomas Weiskel investigates the concept of the sublime in the poetry of English Romantic writers. His work infuses elements of structuralism and psychological thought in his attempt to describe and demystify the sublime experience-or, in his words, to "desublimate the sublime." In doing so, he demonstrates that the sublime is largely mystified, and he contrasts those with faith in the awesomeness of sublimation and those who remain skeptical of the sublime's mystifying power. In working to demystify the sublime, Weiskel emphasizes the task of intelligence by assigning morality and intellect the value of mistrust in sublimation.